DAMA/LIBRA results and perspectives of the second stage - R. Bernabei; P. Belli; F. Cappella; V.Caracciolo; R. Cerulli; C. J. Dai; A. d`Angelo; A. Di Marco; H. L. He; A. Incicchitti; X. H. Ma; F. Montecchia; et al. (Ядерна фізика та енергетика)
The DAMA/LIBRA experiment is mainly dedicated to the investigation on DM particles in the Galactic halo by exploiting the model independent Dark Matter (DM) annual modulation signature. The present DAMA/LIBRA and the former DAMA/NaI (exposed masses: about 250 kg and about 100 kg of highly radiopure NaI(Tl), respectively) experiments have released so far a total exposure of 1.17 t · yr collected over 13 annual cycles; they provide a model independent evidence of the presence of DM particles in the galactic halo at 8.9  C.L. The data of another annual cycle in the same DAMA/LIBRA running conditions are at hand. After the substitution (at fall 2010) of all the photomultipliers (PMTs) with new ones, having higher quantum efficiency, DAMA/LIBRA has entered the phase 2; that substitution has allowed to lower the software energy threshold of the experiment in the present data taking. Future perspectives are mentioned.